The Relationship between Blood Pressure Level and Serum Uric Acid concentration in Hemodialysis Patients - العبود مراد; حسين سعيد; أكرم جحجاح (Latakia University Journal -Medical Sciences Series, 2023)
Introduction: High blood pressure is a common condition in hemodialysis patients. Also, Uric acid is high in these patients due to decreased clearance. Objective: The goal of this investigation was to evaluate the impact of high uric acid level on blood pressure in these patients. Methods: We studied 99 patients (55 male, 44 female), who undergo hemodialysis sessions regularly in Tishreen University Hospital during the period from 2021 to 2022 . Blood pressure was measured just before, during and after dialysis. Uric acid levels were measured just before and after hemodialysis. with monitoring of incidence of IDH if it happened and periodic blood tests.. Results : The median age was 51±15.1 years. The median dialysis duration was 48 months. 63 (63.6%) of patients had serum uric acid ≥6 mg/dl. Before dialysis 61 (61.6%) and 22 (22.2%) had high systolic blood and diastolic blood pressures respectively. Also, 50 (50.5%) had high mean arterial pressure (MAP). Additionally 56 (56.5%) developed inter-dialysis hypotension. After measuring odds ratio for hyperuricemia in each group, we observed low risk of hypruricemia in the group with high systolic pressure (OR = 0.431; P = 0.02), high diastolic pressure (OR = 0.528; P = 0.054),the high MAP group (OR = 0.833; P = 0.01) and IDH group (OR = 0.622; P = 0.03). UA levels were higher in patients receiving dialysis for longer time periods. There was no association between high uric acid level and diastolic pressure (P = 0.054). No relationship was found between serum uric acid and URR (P = 0.8) and body mass index (BMI) (P = 0.4). Conclusion: This study showed paradoxical association between high uric acid level and high systolic pressure, high MAP and IDH.